Analisis Efisiensi Teknik Usaha Budidaya Pembesaran Ikan Kerapu dalam Keramba Jaring Apung di Perairan Teluk Lampung: Produktivitas, Faktor-faktor yang Mempengaruhi dan Implikasi Kebijakan Pengembangan Budidayanya - Tajerin Tajerin; Mohammad Noor (Universitas Islam Indonesia, 2005)
Level of technical efficiency in fish culture reflecting the fish farmer achievement correlated with its managerial competency to managing the principle factors affected per¬formance of productivity its culture fish farming. The research aimed to evaluated level of technical efficiency (productivity) of grouper fish growth out culture, factors affecting and its policy implication. The research was conducted in Lampung Province during September to December 2002. The area sample was selected by purposively in Padang Cermin Sub dis¬trict, South Lampung and the respondent of fish farmer was selected by census method. The result of research showed that average of technical efficiency level received by grouper fish farmers in floating net cages was 0.76 and relatively smooth (coefficient of variation is 0.18). Principle factors affecting technical efficiency was sections level of income from farming fish culture. Considered level of technical efficiency was received come near to frontier, policy implication of culture development should be conducted using extensive approach. Besides need consideration of a matter motivated for consolidation fish farming culture spread based; and that approach will be affected if development really imperative and innovate.Keywords: Technical Efficiency, Frontier Production, Grouper Growth Out